The Role of Accounting in the Most Adverse Conditions of Life: The Diary of a P.O.W. - Diakomihalis, Mihail (Richtmann Publishing, 2022)
The purpose of the paper is to reveal and demonstrate the importance of accounting in everyday life and particularly in the most adverse conditions of life, through the investigation of the diary of a Prisoner of War (P.O.W.). The author of the diary is a young individual who was an ex- WWII captive and consequently refugee in a concentration camp in Italy, in 1945, with elementary education but absolutely â€œilliterateâ€ in accounting and economics issues. The handwritten diary of the P.O.W. is the core research evidence used, along with the existing literature regarding accounting in everyday life, including accounting histories of war. Additionally, the study draws on new research firmly embedded in everyday transactions. The detailed analysis of the diary reveals the contribution of improvised and self-taught bookkeeping, to the strengthening of the feeling of survival, the acquisition of the necessary and most asset, the achievement of the insatiable desire of repatriation and finally the acceptance of the patent defect caused from an impairment, through foresight to deal with it. The fulfillment of all the mentioned above aspiration supports that basic accounting knowledge, deriving from the needs of the individual according to specific circumstances of time and place, may be more than satisfied to record simple daily transactions, even by illiterate people. Received: 24 January 2022 / Accepted: 28 February 2022 / Published: 5 March 2022